Analisis Respon Pengusaha Konstruksi terhadap Beroperasinya Bank Syari'ah - Hardiwinoto Hardiwinoto (STIE Widya Manggala, 2010)
The aim of the research was to analyze empirically about factors influencing entrepreneurs attitude to respond the operating syari’ah bank round Semarang and Demak. There were two variables, the first was dependent variable means entrepreneur attitude andthe second was independent variables which had three understanding level. There are the understanding level of religion (religiousity), financial mechanism of syari’ah bank, and syari’ah bank product. The population in research was the member of GAPENSI (AlianceExecutor of Contruction National Indonesia) Semarang and Demak. There were the directors or the company head who has authority in making financial decision. The method used in this hypothesis examination was linear regresion to test the independent variables influence todependent variable. The result of research indicat that result of F count equal to 19.384 at level of significancy 0.000 by together. While each independent variable had own significancy level of religiousity significance 0.926 accepted at trust boundary 0.10, financial mechanismof syari’ah bank significance 0.022 accepted at trust boundary 0.05, and syari’ah bank product significance 0.001 accepted at trust boundary 0.001.